(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2024)
The purpose of this descriptive observational research was to assess the clinic epidemiological profile and seroprevalence of chronic hepatitis (HBV) and hepatitis C (HCV) in patients at Government Medical College and Memorial Government Hospital in Haldwani, Uttarakhand. and 141 HCV-positive patients (1.97%) during a two-year period. 141 HCV-positive cases (1.97%) and thorough data were used to evaluate the patients. Laboratory testing, imaging investigations, and thorough clinical assessments were used to evaluate the patients; SPSS was used to analyze the data. While HBV patients had substantially higher serum bilirubin (p=0.005) and SGOT levels (p=0.0057), most HCV patients had advanced liver disease, as shown by higher rates of ascites (13.97%), jaundice (11.73%), and increased urea levels (p=0.03). Age, gender, and education did not significantly vary across groups, according to sociodemographic analysis; however, geographic patterns indicated that HBV was more common in Nainital (63.2%) and HCV was more common in Udham Singh Nagar (27.7%) and Bijnor (29.1%). These results highlight the critical need for focused interventions to lower the incidence of viral hepatitis in marginalized communities, such as awareness campaigns, preventative measures, and region-specific healthcare initiatives.